Analisis Kebutuhan Materi Pengajaran Qawa'id Berbasis Multimedia Interaktif untuk Tingkat Pemula - Siti Masyitoh; Rifda Haniefa; Samsi Setiadi; Ihwan Rahman Bahtiar; Puti Zulharby (JURNAL PENA, 2026)
This study aims to analyze the need for developing interactive multimedia–based Qawa’id instructional materials for beginner-level students in the Arabic Language Education Program at Universitas Negeri Jakarta. The research focuses on the needs analysis stage as an initial foundation for instructional material development. Data were collected through questionnaires, classroom observations, interviews, and document analysis involving 120 first-year students. The findings indicate that Qawa’id instruction still faces various challenges, particularly related to the limitations of instructional materials and learning media that tend to be theoretical and text-based, thereby hindering students’ understanding of abstract grammatical concepts. Questionnaire results reveal a very high level of need and interest in interactive multimedia–based Qawa’id materials that integrate visual, audio, animation, and interactive exercises. In addition, students demonstrate strong readiness to independently utilize digital instructional materials outside the classroom. Qualitative findings support the quantitative results, showing that visualization and contextual presentation enhance student engagement and comprehension. Based on these findings, it can be concluded that the development of interactive multimedia–based Qawa’id instructional materials is an urgent and strategic necessity to improve the effectiveness of Qawa’id learning for beginner students and to serve as a conceptual foundation for the subsequent stages of instructional material development.